Fabrication of Ti-25Ni-25W Alloy by Mechanical Alloying and Spark Plasma Sintering for Biomedical Applications. (2018) - Singh, Navdeep; Kumar, Harmesh
Abstract: This research work is carried out to successfully manufacture a modern range of β-type Ti-25Ni-25W alloy by mechanical alloying and spark plasma sintering (SPS) approach. In this research work, the impact of pressure and sintering temperature on the mechanical properties and microstructure of the sintered alloy was studied. The field-emission scanning electron microscopy and energy-dispersive X-ray spectroscopy were used to inspect the surface topography and elemental composition of the sintered Ti-25Ni-25W alloy. The Vickers hardness tester was used to calculate the micro-hardness of the manufactured alloy. Meanwhile the sintering process of Ti-25Ni-25W alloy, it is detected that the complicated reactions between the W and alloying elements takes place. Biocompatible phases (W2 C0.84, Ni2 Ti, and Ni3 C) are developed with the help of these complicated reactions. These biocompatible phases are favorable for formation of apatite and also enhances the bioactivity of the alloy for osseointegration. The maximum value of micro-hardness shown by manufactured Ti-25Ni-25W alloy is 617 HV. The manufactured Ti-25Ni-25W alloy exhibits very high micro-hardness value as compared to the alloys described in literature. The observations are drawn from the current research work is that the β-type Ti alloy (Ti-25Ni-25W) is recommended as a material for biomedical applications